(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to determine how peer pressure influences student performance in class. Peer pressure is one of the powerful forces that influence teenagers. This closeness of peer pressure severely impacts students’ performance since it can lead to students skipping courses and absenteeism. On the other hand, peer groups can help a youngster develop skills that will help him perform better in class. Negative peer pressure may encourage students to engage in vices such as drinking, smoking, or using drugs, as well as other variables that lead to absenteeism or cutting classes, lowering their academic performance. Peer pressure also has a significant positive impact on young people’s education. Teenagers’ brains show greater activity when their classmates observe them. Seeing one’s peers achieve their objectives can motivate one to be more determined and goal-oriented. The researchers use a descriptive method design to collect information about the Peer Pressure That Affects the Academic Performance of Grade 12 Humanities and Social Sciences Students. The researchers intended to fifty (50) sample grade 12 HUMSS students, which came from the total population of the Humanities and Social Sciences Department of Bestlink College of the Philippines during the school year 2021-2022. Based on the study’s results, peer pressure affects academic performance in factors such as supporting your friends helps you to have better academic performance. It implies that supporting your friends helps you perform better academically. The respondents always encounter it, and the friends’ effects on doing your academic work are the problems encountered sometimes by the respondents. In challenges Hard time communicating with classmates/schoolmates – the challenges students might experience in peer pressure is the problem sometimes encountered by the respondents. The researchers recommend that students search for topics mostly related to student pressure. It is recommended that teachers guide the students and teach time the positive and negative peer pressure and how they can help it in themselves.